Insulin-like Growth Factor Binding Protein 2 predicts mortality risk in heart failure. (1st February 2020) - Barutaut, Manon; Fournier, Pauline; Peacock, William F.; Evaristi, Maria Francesca; Caubère, Céline; Turkieh, Annie; Desmoulin, Franck; Eurlings, Luc W.M.; van Wijk, Sandra; Rocca, Hans-Peter Brunner-La; Butler, Javed; Koukoui, François; et al.
Abstract: Background: Insulin-like Growth Factor Binding Protein 2 (IGFBP2) showed greater heart failure (HF) diagnostic accuracy than the "grey zone" B-type natriuretic peptides, and may have prognostic utility as well. Objectives: To determine if IGFBP2 provides independent information on cardiovascular mortality in HF. Methods: A retrospective study of 870 HF patients from 3 independent international cohorts. Presentation IGFBP2 plasma levels were measured by ELISA, and patients were followed from 1 year (Maastricht, Netherlands) to 6 years (Atlanta, GA, USA and Toulouse, France). Multivariate analysis, Net Reclassification Improvement (NRI) and Integrated Discrimination Improvement (IDI) were performed in the 3 cohorts. The primary outcome was cardiovascular mortality. Results: In multivariate Cox proportional hazards analysis, the highest quartile of IGFBP2 was associated with mortality in the Maastricht cohort (adjusted hazard ratio 1.69 (95% CI, 1.18–2.41), p = 0.004) and in the combined Atlanta and Toulouse cohorts (adjusted hazard ratio 2.04 (95%CI, 1.3–3.3), p = 0.003). Adding IGFBP2 to a clinical model allowed a reclassification of adverse outcome risk in the Maastricht cohort (NRI = 18.7% p = 0.03; IDI = 3.9% p = 0.02) and with the Atlanta/Toulouse patients (NRI of 40.4% p = 0.01, 31, 2% p = 0.04, 31.5% p = 0, 02 and IDI of 2, 9% p = 0, 0005, 3.1% p = 0, 0005 and 4, 2%, p = 0.0005, for a follow-up of 1, 2 and 3 years, respectively). Conclusion: In 3 international cohorts, IGFBP2 level is a strong prognostic factor for cardiovascular mortality in HF, adding information to natriuretic monitoring and usual clinical markers, that should be further prospectively evaluated for patients' optimized care. Highlights: Heart failure (HF) current median survival rate is <5 years. Insulin-like Growth Factor Binding Protein 2 (IGFBP2) is a HF diagnostic biomarker. IGFBP2 has greater diagnostic accuracy than "grey zone" natriuretic peptides. IGFBP2 is a predictor for mortality in chronic and acute heart failure patients. IGFBP2 adds prognostic value to natriuretic peptides and clinical data.